ECOLOGY OF HUMAN HEALTH - REQUIRED Conditions for sustainable development - D. Y. Anashkin; A. V. Smirnov (Научный вестник МГТУ ГА, 2016)
The article discusses the health problems as an indicator of society's transition to Sustainable Development, which is analyzed as a complex health criterion for the quality of the environment and as a social value.